Correction: Oxygen diffusion in single crystal barium titanate. Issue 46 (19th November 2018) - Kessel, Markus; De Souza, Roger A.; Martin, Manfred
Abstract : Correction for 'Oxygen diffusion in single crystal barium titanate' by Markus Kessel et al., Phys. Chem. Chem. Phys., 2015, 17, 12587–12597.